ADOPTION OF BIOSECURITY MEASURES BY LAYER SMALLHOLDERS - Lestari, V.S.; Sirajuddin, S.N.; Kasim, K. (Diponegoro University, 2011)
It was indicated that layer smallholders awareness of biosecurity was low. This paper aimed todetermine the level of adoption within the South Sulawesi layer smallholders of a range of standardbiosecurity measures. Sidenreng Rappang (Sidrap) regency was chosen as a location of the research,because it was famous as a central of layer smallholders. Total sample was 60 respondents. The samplewas chosen through random sampling from two districts which were the most populous of layersmallholders, namely Baranti and Maritengae. Data were collected using structured questionnaires anddepth-interview. The data were tabulated and analysed using a simple method of scoring with regard totheir biosecurity status. The status of biosecurity was used to know the level of biosecurity adoption.Biosecurity status was obtained based on the adoption of biosecurity measures which consisted of 9stages: farm inputs, traffic onto farms, distance from sources of pathogens to shed, exposure of farm,biosecurity at farm boundary, biosecurity between farm boundary and shed, biosecurity at the shed door,traffic into the shed and susceptibility of the flock. Using adoption index, this research revealed thatbiosecurity adoption of layer smallholders in South Sulawesi was classified into a “partial adopter”.